2021
DOI: 10.17159/2224-7912/2021/v61n2a10
|View full text |Cite
|
Sign up to set email alerts
|

Die verband tussen ouerskapspraktyke en die aggressiewe gedrag van leerlinge met matige intellektuele disfunksie

Abstract: Onderwysdepartement en vir die afgelope 23 jaar betrokke by spesiale onderwys vir leerlinge met matige intellektuele disfunksie. Sy verwerf 'n PhD in Vroeë Kinderontwikkeling aan die Universiteit van Pretoria. Haar navorsingsfokus is die aggres siewe gedragsuitvalle van leerlinge met matige intellektuele disfunksie. MELANIE MOEN is senior dosent verbonde aan die Universiteit van Pretoria. Sy het 'n PhD in Opvoedkundige Sielkunde van die Universiteit van Pretoria. Haar navorsingsareas is familiemoord, jeugmisda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Thus, it is unsurprising that learners who grow up in destructive environments at home tend to be influenced by what they see at home and become violent themselves (Roberts, Pullig, and David 2019). As with other studies on learner aggression in different contexts, the findings of this study point out that learners experiencing violence tend to replicate aggressive behaviours that they were exposed to in their homes (Cockrell and Moen 2021;Esposito et al 2022;Khumalo 2019). The findings also corroborate previous studies that have shown that learners from disruptive family environments are sometimes very limited when it comes to mechanisms that can be used to cope with stressors, and aggression is usually their only known response to stressors (Stewart et al 2022;van Bruwaene et al 2020).…”
Section: Disruptive Family Circumstancessupporting
confidence: 70%
See 1 more Smart Citation
“…Thus, it is unsurprising that learners who grow up in destructive environments at home tend to be influenced by what they see at home and become violent themselves (Roberts, Pullig, and David 2019). As with other studies on learner aggression in different contexts, the findings of this study point out that learners experiencing violence tend to replicate aggressive behaviours that they were exposed to in their homes (Cockrell and Moen 2021;Esposito et al 2022;Khumalo 2019). The findings also corroborate previous studies that have shown that learners from disruptive family environments are sometimes very limited when it comes to mechanisms that can be used to cope with stressors, and aggression is usually their only known response to stressors (Stewart et al 2022;van Bruwaene et al 2020).…”
Section: Disruptive Family Circumstancessupporting
confidence: 70%
“…According to Prot et al (2016), while the effects of media may not be immediate, they can accumulate over time and produce significant behavioural changes that impact both learners and teachers. Exposure to media violence has been found to increase aggressive behaviours in school-aged adolescent learners (Cockrell and Moen 2021). Anderson et al (2015) similarly found that media violence can increase aggressive perceptions, feelings, and behaviours while decreasing empathy.…”
Section: Media-related Factorsmentioning
confidence: 96%